ANALYSIS EARLY DETECTION OF GROWTH AND DEVELOPMENT CHILDREN BY PRE – SCREENING QUESTIONNAIRE OF DEVELOPMENT (KPSP) AT CENTRAL JAKARTA IN OCTOBER 2017 - Nova Yulianti; Putri Argianti; Lily Herlina; Siti Nur Indah Oktaviani (Universitas Muhammadiyah Kudus, 2018)
ABSTRACTBackground. Indonesia is a developing country which is one of 117 countries that has three nutritional problems in toddlers namely stunting, wasting and overweight. Based on data of Basic Health Research (Riskesdas) on 2013 prevalence malnutrition in Indonesia has increased 1.7%. Approximately 16% of toddler experience motor development disorder and 1: 100 children have less intelligence and speech delay. The process of early detection and stimulation of growth and development into things that should not be underestimated in order to create a generation of quality successors who are able to grow and develop well. Early detection of growth and development is one effort that can be done early childhood teachers, mothers and teachers to detect any behavioral drift of growth.Methodology. This research used cross sectional with observational approach. Determination of location and sample using purposive sampling in BKB PAUD Serdang Urban Village Kemayoran Central Jakarta with sample amount 95 childrenResult. Showing that of 95 children 58 (61%) female and 37 (39%) men. Age of child in early childhood is highest in 4 - 5 years amounted to 35 (36.8%) and 2 - 3 years amounted to 6 (6.3%). 1 Nutrition status was found less than 34 (37,9%), more nutrition 6 (6,3%) and Obesity 6 (6,3%). The results of early detection of child deviation by using Pre-Screening Development Questionnaire (KPSP) as many as 85 (89.5%) in accordance with the development, but there are 7 (7.4%) doubtful children and 3 (3.2) possibility of deviation.Key words. PAUD, KPSP